Question
upstudy study bank question image url

b) \( 3\left(\cos ^{4} x+\sin ^{4} x\right)-2\left(\cos ^{6} x+\sin ^{6} x\right)=1 \)

Ask by Hardy Bartlett. in Turkey
Nov 25,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

Dengle, her \(x\) için doğru.

Solution

Verilen denklemi inceleyelim: \[ 3\left(\cos ^{4} x+\sin ^{4} x\right)-2\left(\cos ^{6} x+\sin ^{6} x\right)=1 \] Öncelikle, \(\cos^4 x + \sin^4 x\) ve \(\cos^6 x + \sin^6 x\) ifadelerini daha basit hale getirelim. \(\cos^4 x + \sin^4 x\) ifadesini şu şekilde yazabiliriz: \[ \cos^4 x + \sin^4 x = (\cos^2 x + \sin^2 x)^2 - 2\cos^2 x \sin^2 x = 1 - 2\cos^2 x \sin^2 x \] Burada \(\cos^2 x + \sin^2 x = 1\) özelliğini kullandık. Şimdi \(\cos^6 x + \sin^6 x\) ifadesini yazalım: \[ \cos^6 x + \sin^6 x = (\cos^2 x + \sin^2 x)(\cos^4 x + \sin^4 x - \cos^2 x \sin^2 x) = 1 \cdot \left((1 - 2\cos^2 x \sin^2 x) - \cos^2 x \sin^2 x\right) \] Bu ifadeyi sadeleştirirsek: \[ \cos^6 x + \sin^6 x = 1 - 3\cos^2 x \sin^2 x \] Şimdi bu iki ifadeyi denkleme yerleştirelim: \[ 3(1 - 2\cos^2 x \sin^2 x) - 2(1 - 3\cos^2 x \sin^2 x) = 1 \] Bu ifadeyi açalım: \[ 3 - 6\cos^2 x \sin^2 x - 2 + 6\cos^2 x \sin^2 x = 1 \] Buradan: \[ 1 - 6\cos^2 x \sin^2 x + 6\cos^2 x \sin^2 x = 1 \] Sonuç olarak: \[ 1 = 1 \] Bu, her \(x\) için doğru olan bir eşitliktir. Yani, verilen denklem her \(x\) için doğrudur.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( 3(\cos^4 x + \sin^4 x) - 2(\cos^6 x + \sin^6 x) = 1 \), we can utilize trigonometric identities and algebraic manipulation. First, we recognize the identities involving powers of sine and cosine. We start by expressing \( \cos^4 x + \sin^4 x \) and \( \cos^6 x + \sin^6 x \) using the formulas for sums of squares: 1. **Using the identity**: \[ \cos^4 x + \sin^4 x = (\cos^2 x + \sin^2 x)^2 - 2\cos^2 x \sin^2 x = 1 - 2\cos^2 x \sin^2 x \] Therefore, \[ 3(\cos^4 x + \sin^4 x) = 3(1 - 2\cos^2 x \sin^2 x) = 3 - 6\cos^2 x \sin^2 x \] 2. **For the sixth power term**, we can use a similar approach: \[ \cos^6 x + \sin^6 x = (\cos^2 x + \sin^2 x)(\cos^4 x + \sin^4 x) - \cos^2 x \sin^2 x(\cos^2 x + \sin^2 x) = 1(1 - 2\cos^2 x \sin^2 x) - \cos^2 x \sin^2 x \] Thus, \[ \cos^6 x + \sin^6 x = 1 - 3\cos^2 x \sin^2 x \] Accordingly, \[ 2(\cos^6 x + \sin^6 x) = 2(1 - 3\cos^2 x \sin^2 x) = 2 - 6\cos^2 x \sin^2 x \] 3. **Substituting these into the original equation**, we get: \[ 3 - 6\cos^2 x \sin^2 x - (2 - 6\cos^2 x \sin^2 x) = 1 \] Simplifying this gives: \[ 3 - 2 - 6\cos^2 x \sin^2 x + 6\cos^2 x \sin^2 x = 1 \] Which simplifies to: \[ 1 = 1, \] showing that the equation holds for any value of \( x \). Consequently, the equation \( 3(\cos^4 x + \sin^4 x) - 2(\cos^6 x + \sin^6 x) = 1 \) is an identity and is true for all real numbers \( x \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy